Beach and Indoor Volleyball Athletes Present Similar Lower Limb Muscle Activation During a Countermovement Jump - Aedo-Munoz, E (University School of Physical Education in Wroclaw, 2020)
Purpose. The study aimed to compare and correlate the power, height, eccentric and concentric force development rate of 3 sequential attempts of countermovement jump (CMJ) and the respective muscle response in beach and indoor volleyball athletes. Methods. The sample involved high-level hard court indoor volleyball (HCIV, n = 7) and high-level sand court beach volleyball (SCBV, n = 6) athletes. They performed 3 CMJs (1st CMJ vs. 2nd CMJ vs. 3rd CMJ) to determine the height, eccentric force development rate (EFDR), concentric force development rate (CFDR), power, and lower limbs muscle electrical activity. Results. Difference was demonstrated between HCIV vs. SCBV players in 3rd CMJ EFDR (-270.2 ± 31.6 N/s vs. -214.3 ± 38.7 N/s). In HCIV, 1st CMJ was different from 2nd CMJ and 3rd CMJ in EFDR (-239.0 ± 27.3 N/s vs. -285.6 ± 40.2 N/s and -270.2 ± 31.6 N/s), CFDR (87.8 ± 24.4 N/s vs. 89.6 ± 25.7 N/s and 75.0 ± 23.6 N/s), and power (2341.8 ± 342.3 W vs. 2433.9 ± 327.2 W and 2411.0 ± 358.5 W). In SCBV, 2nd CMJ was different from 3rd CMJ in EFDR (-267.1 ± 45.2 N/s vs. -214.3 ± 38.7 N/s). In 2nd CMJ, the left gluteus presented lower electrical activity than the left medial gastrocnemius, and HCIV revealed a difference between the response of the right and left gluteus in 3rd CMJ. Conclusions. Our analysis demonstrated ca. 70% of good or excellent intra-class correlation between the beach and indoor groups. © 2020 University School of Physical Education in Wroclaw. All rights reserved.